Chemically synthesized Cu2Te incorporated Bi-Sb-Te p-type thermoelectric materials for low temperature energy harvesting. (May 2019) - Song, Jae Min; Rahman, Jamil Ur; Cho, Jung Young; Lee, Soonil; Seo, Won Seon; Kim, Seyun; Kim, Sang-il; Lee, Kyu Hyoung; Roh, Dongkyu; Shin, Weon Ho
Abstract: We report a facile and efficient way to enhance and modulate thermoelectric performance by incorporating chemically synthesized Cu2 Te nanoparticles on p-type Bi0.5 Sb1.5 Te3 matrix. By varying the amount of Cu2 Te nanoparticles, the temperature of maximum thermoelectric performance shifted systematically from room temperature to 425 K. The highest figure-of-merit value, 1.1, was achieved at 377 K by incorporating 0.1 wt% Cu2 Te nanoparticles in Bi0.5 Sb1.5 Te3 matrix, which is due to enhancement in power factor and reduction in lattice thermal conductivity. The results demonstrate that Cu2 Te incorporation could be an effective strategy for Bi-Te based thermoelectric power generation. Graphical abstract: Unlabelled Image